2017
DOI: 10.3947/ic.2017.49.2.123
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculous Meningitis-Mimicking Varicella-Zoster Meningitis

Abstract: BackgroundVaricella-zoster virus (VZV) is one of the most common etiologies of aseptic meningitis. The severest manifestation of VZV meningitis is occasionally confused with tuberculous meningitis (TBM). Thus, we investigated the clinical manifestations of VZV meningitis as compared with those of TBM.Materials and MethodsAll adult patients who were diagnosed with VZV meningitis or TBM were enrolled at a tertiary hospital in Seoul, South Korea, during an 8-year period. The clinical characteristics and cerebrosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…Also, this evinces the possibility of the existence of a significant difference between the actual diagnosis and the clinician’s diagnosis based on the empirical belief that meningitis with lymphocyte-dominant pleocytosis and elevated CSF-ADA level is TBM. These results are consistent with a series of prior studies that have reported elevated ADA levels in patients with VM ( Cho et al., 2013 ; Ekermans et al., 2017 ; Hong et al., 2017 ). Hong et al.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Also, this evinces the possibility of the existence of a significant difference between the actual diagnosis and the clinician’s diagnosis based on the empirical belief that meningitis with lymphocyte-dominant pleocytosis and elevated CSF-ADA level is TBM. These results are consistent with a series of prior studies that have reported elevated ADA levels in patients with VM ( Cho et al., 2013 ; Ekermans et al., 2017 ; Hong et al., 2017 ). Hong et al.…”
Section: Discussionsupporting
confidence: 93%
“…reported a study that compared CSF-ADA levels of VZV meningitis, VZV meningitis previously misdiagnosed as true TBM. In that study, the ADA level of the misdiagnosed groups (range, 8.0–15.0 IU/L) overlapped with that of the true TBM group (range, 11.7–31.6 IU/L), while the proportion of lymphocytosis (median, 83% versus 60% in the misdiagnosis versus the true TBM group, respectively; p < 0.001) was the significant difference between the misdiagnosed and true TBM groups ( Hong et al., 2017 ). Clinicians should be aware that misdiagnosis and inappropriate treatment of meningitis can occur if they depend heavily on the ADA findings when patients are without etiology-specific symptoms or signs.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Since the number of cases was not large enough, only a limited number of features known as useful characteristics for differentiating between TBM and VM were searched and included in the analysis because of the overfitting concern. Based on the previous studies, data on age [ 6 ], duration of illness from the appearance of symptoms and onset of signs to hospital visit [ 7 ], vomiting [ 7 ], neurologic symptoms and signs [ 6 ], serum sodium [ 6 ], CSF glucose [ 8 ], CSF protein[ 8 ], and CSF adenosine deaminase (ADA) [ 9 ] were collected as discriminative features for machine-learning. Neurologic symptoms and signs were defined according to one of the following symptoms or signs: lethargy, confusion, cranial nerve palsy, hemiparesis, delirium, stupor, coma, seizures, hemiplegia, or paraparesis [ 6 ].…”
Section: Methodsmentioning
confidence: 99%